Improvements in experimental investigation of molten Mg-based materials. (15th December 2018) - Kudyba, Artur; Sobczak, Natalia; Budzioch, Janusz; Polkowski, Wojciech; Giuranno, Donatella
Abstract: In this paper, the experimental performance of a new testing device designed for investigating the high temperature properties of molten Mg is presented. The newly developed device allows examining high temperature wetting behavior and thermophysical properties of molten Mg (and Mg alloys) by using various experimental procedures (e.g. classical sessile drop, pendant drop, dispensed drop and drop sucking). High temperature wettability tests at temperatures up to 1000 °C in an inert gas atmosphere or under high vacuum (up to 10 −7  hPa) are now possible. It has been documented that the application of the classical sessile drop method combined with a capillary purification procedure successfully eliminates the problem of magnesium oxidation that traditionally affects obtained results. Selected examples of high temperature experiments carried out for molten Mg in contact with various refractories are presented in order to show a wide range of analytical possibilities of the new device. The results obtained by using the new device are important from both a high theoretical and practical perspective regarding liquid phase assisted fabrication and processing of Mg-based alloys and metal-matrix composites. Graphical abstract: